Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/jn.00420.2014
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the evolution of crossmodal plasticity and visual functions before and after sight restoration

Abstract: Visual deprivation leads to massive reorganization in both the structure and function of the occipital cortex, raising crucial challenges for sight restoration. We tracked the behavioral, structural, and neurofunctional changes occurring in an early and severely visually impaired patient before and 1.5 and 7 mo after sight restoration with magnetic resonance imaging. Robust presurgical auditory responses were found in occipital cortex despite residual preoperative vision. In primary visual cortex, crossmodal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 71 publications
0
25
0
2
Order By: Relevance
“…The spared plasticity of V1 and low tier associative cortices was not expected, given the prevailing evidence of low plasticity to visual stimuli observed in the two subjects who regained vision at adult age [13,26]. However, both of these studies followed the progression of congenitally blind patients or patients who became blind during the critical period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spared plasticity of V1 and low tier associative cortices was not expected, given the prevailing evidence of low plasticity to visual stimuli observed in the two subjects who regained vision at adult age [13,26]. However, both of these studies followed the progression of congenitally blind patients or patients who became blind during the critical period.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the degree of vision loss in retinitis pigmentosa (RP) patients correlates with primary visual cortical responses to tactile stimuli [23,24]. Interestingly, in one case of restored vision (Boston Keratoprostesis, see [25]), responses to motion stimuli were enhanced in extra-striate occipital areas seven months after visual restoration, and this was accompanied by a decreased recruitment of acoustic processing [26]. All these data suggest that, after the original input is restored, the brain needs time to promote a response to the original sensation.…”
Section: Introductionmentioning
confidence: 99%
“…Patient MM became blind at the age of three years old, and once his sight was restored in his 40ies, he was only able to recover visual abilities strictly related to the visual experience before blindness, such as perception of simple forms, color and motion, while perception of more complex 3D forms, objects and faces remained severely impaired even after several years of restored vision (Fine et al, 2003;Huber et al, 2015). fMRI studies on patient MM and on another early-blind patient whose vision was partially restored in adulthood, showed that cortical plasticity was also limited although not completely absent: several months after vision restoration, cross-modal auditory responses continued to coexist with the restored visual activations in area V1 (Dormal et al, 2015) and MT (Saenz et al, 2008). Interestingly however Dormal et al (2015) observed that cross-modal responses in extra striate areas decreased after surgery and vision improved suggesting that cross-modal reorganization can be partially reversed in their early-blind patient.…”
Section: Cortical Plasticity After Sight Restorationmentioning
confidence: 96%
“…However, several recent lines of evidence have put this assumption into question: in animal models, ocular dominance plasticity can be reactivated after the closure of the critical period by manipulating the visual cortex excitability, either pharmacologically or through environmental enrichment and physical activity (Baroncelli et al, 2010(Baroncelli et al, , 2012Berardi et al, 2015;Harauzov et al, 2010;He et al, 2006;Hensch and Fagiolini, 2005;Hensch et al, 1998;Maya Vetencourt et al, 2008;Pizzorusso et al, 2002;Sale et al, 2007Sale et al, , 2014Spolidoro et al, 2009). In adult humans, evidence of preserved visual plasticity has been demonstrated by behavioral and neural changes associated with perceptual learning (Beyeler et al, 2017;Dosher and Lu, 2017;Fiorentini and Berardi, 1980;Watanabe and Sasaki, 2015), short term visual deprivation (Binda et al, 2018;Binda and Lunghi, 2017;Lunghi et al, 2011Lunghi et al, , 2013Lunghi et al, , 2015aLunghi et al, ,b, 2018Lunghi and Sale, 2015;Zhou et al, 2013Zhou et al, , 2014, progressive blinding pathologies and visual restoration therapies (Aguirre et al, 2016;Baseler et al, 2011a;Burton, 2003;Castaldi et al, 2016;Cunningham et al, 2015a,b;Dormal et al, 2015;Heimler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One study conducted in monkeys that were deprived of vision during the first year of life demonstrated that the posterior parietal association cortex (BA7) loses its responsiveness to visual stimulation but responds to tactile stimulation and active somatic exploration even 1 year after restored vision [28]. Two previous studies in humans demonstrated that auditory and visual activity may co-exist in occipital regions after sight-restoration [29,30]. However, these studies were carried out in patients who reacquired sight after a lifelong history of visual deprivation.…”
mentioning
confidence: 99%